KESALAHAN PENYUSUNAN TEKS EDITORIAL SISWA KELAS XII SMA NEGERI 9 MAKASSAR - Putri Fadillah Amini R. Chaniago; Ramly Ramly; Abdul Azis (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the form of spelling, and diction in the preparation of editorial texts prepared by class XII students of SMA Negeri 9 Makassar. This research uses descriptive qualitative research. The data in this study are students' editorial text writings that contain sentence errors in the editorial text structure, namely opinion statement, argumentation, and reaffirmation of opinion. The data source in this study is the results of students' editorial text writing. data analysis is done by data collection, data reduction, data presentation, and conclusion drawing. The results of the study revealed that the analysis of students' editorial text preparation errors was found to be varied which included spelling errors, diction errors and paragraph errors. Spelling errors can be in the form of errors in the use of capital letters, the use of italics, writing derivative words, writing abbreviations and acronyms, using full stops, using commas, using dashes, and writing prepositions. Diction errors are in the form of word accuracy, word rigidity, word simplicity, and word prevalence. Paragraph Errors can be seen from the completeness of the paragraph.